1999
DOI: 10.1152/ajpendo.1999.277.5.e920
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces insulin resistance independent of changes in interstitial insulin

Abstract: We set out to examine whether angiotensin-driven hypertension can alter insulin action and whether these changes are reflected as changes in interstitial insulin (the signal to which insulin-sensitive cells respond to increase glucose uptake). To this end, we measured hemodynamic parameters, glucose turnover, and insulin dynamics in both plasma and interstitial fluid (lymph) during hyperinsulinemic euglycemic clamps in anesthetized dogs, with or without simultaneous infusions of angiotensin II (ANG II). Hyperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 29 publications
3
80
0
1
Order By: Relevance
“…Results of the present investigation are consistent with and complement the findings of Richey et al 23 These investigators demonstrated that acute infusion of Ang II into normal dogs during euglycemic, hyperinsulinemic clamp led to a significant decrease in insulin sensitivity and that this Ang II-induced insulin resistance probably developed because of direct inhibition of glucose transport by the myocyte. Our findings that the acute administration of irbesartan, which would prevent any negative action of Ang II on cellular glucose transport, led to an enhancement of insulinstimulated skeletal-muscle glucose transport (at least in type I muscle), is entirely consistent with this hypothesis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Results of the present investigation are consistent with and complement the findings of Richey et al 23 These investigators demonstrated that acute infusion of Ang II into normal dogs during euglycemic, hyperinsulinemic clamp led to a significant decrease in insulin sensitivity and that this Ang II-induced insulin resistance probably developed because of direct inhibition of glucose transport by the myocyte. Our findings that the acute administration of irbesartan, which would prevent any negative action of Ang II on cellular glucose transport, led to an enhancement of insulinstimulated skeletal-muscle glucose transport (at least in type I muscle), is entirely consistent with this hypothesis.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Rao 22 and Richey et al 23 have reported that acute infusion of Ang II leads to substantial reduction in glucose disposal in normal skeletal muscle, which could not be attributed to hemodynamic alterations. 23 To our knowledge, neither the acute effects of specific Ang II receptor antagonism on insulin-stimulated glucose transport in insulin-resistant type I skeletal muscle (eg, soleus) nor the chronic effects of Ang II receptor antagonism on the skeletal-muscle glucose transport system in conditions of insulin resistance have been investigated.In this context, the purpose of the present study was to assess in an animal model of skeletal-muscle insulin resistance, hyperinsulinemia, glucose intolerance, and dyslipidemia (obese Zucker fa/fa rat) the effects of acute or chronic treatment with a specific Ang II receptor (AT 1 -subtype) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…reported a significant increase in plasma Ang II concentrations, 38 which is associated with insulin resistance and impaired glucose homeostasis. 41,42 In addition, in these studies MR blockade was also associated with significantly increased plasma cortisol. As glucocorticoids and mineralocorticoids have similar affinity for MR, it is possible that MR blockade decreases clearance of cortisol, leading to impaired insulin action in numerous tissues such as skeletal muscle, adipose, hepatic and cardiovascular tissues, 43 whole-body insulin resistance and impaired glucose homeostasis.…”
Section: Raas Inhibition In the Clinical Settingmentioning
confidence: 52%
“…It has been shown that Ang II infusion induces insulin resistance as well as a substantial reduction in glucose disposal in normal skeletal muscle (Rao 1994, Richey et al 1999. Conversely, treatment with AT1R blockers enhances insulin sensitivity (Henriksen et al 2001, Shiuchi et al 2004, Muñoz et al 2006.…”
Section: Discussionmentioning
confidence: 99%